Correlation between the level of cholesteryl ester transfer protein in follicular fluid with fertilization rates in IVF/ ICSI cycles - Amir Mehdizadeh; Ali Rahimipour; Laya Farzadi; Masoud Darabi; Amir-Mansour Vatankhah; Zahra Golmohamadi; Mohammad Nouri (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Follicular fluid (FF) plays an important role in oocytes and embryo development, which may contribute to IVF/ICSI success rate. Objective: The aim of this study was to investigate the correlation between cholesteryl ester transfer protein (CETP) level in FF and the success rate of IVF/ICSI.Materials and Methods: In a cross-sectional study, FF samples, FF samples were obtained from 100 patients referred to Tabriz Alzahra Hospital. Seventy-nine subjects underwent IVF and the remaining 21 underwent ICSI. The levels of high-density lipoprotein cholesterol (HDL-C), apolipoprotein A-I and CETP were measured using enzymatic, turbidometric and ELISA methods respectively.Results: Analysis of the subgroups with different levels of CETP showed a significant lower level of CETP in the subgroup with the lowest number of mature oocytes (p<0.05). The level of CETP was also considerably lower (18%, p=0.05) in subjects with<50% oocytes fertilization ratio than subjects with >70% of this ratio.Conclusion: While no association was found for pregnancy, the amount of CETP in FF was associated positively to the maturity and the percentage of oocyte fertilization.